Hubungan Motivasi Pegawai dengan Kelengkapan Dokumentasi di Bidang Kesehatan Masyarakat Dinas Kesehatan Kota Palembang - S, Sunirah; Herdiani, Rini (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Performance is the appearance of the work of personnel both quantity and quality within an organization. The purpose of this study was to determine the relationship between the work environment and incentive providers and employee motivation in completing documentation in the Public Health Sector of the Palembang City Health Office. This study design was an analytical survey with a cross-sectional approach. The population is all employees working in the Public Health Sector of the Palembang City Health Office and community health centers throughout Palembang City and the sample of this study is the total of the population. From the entire analysis process that has been carried out, it can be concluded that the independent variables that are suspected of being related to employee performance are all significantly related to employee motivation, namely from the results of statistical tests with Chi-Square, a p value of 0.010 was obtained where the α value (0.05) is greater than the p value (0.010) which means there is a meaningful relationship between the work environment and employee motivation in the completeness of documentation in the field of public health at the Palembang City Health Service and the results of the statistical test with Chi-Square obtained a p value = 0.000 where the α value (0.05) is greater than the p value (0.000) which means there is a significant relationship between the provision of incentives and employee motivation in the completeness of reporting records in the field of public health at the Palembang City Health Office. The results of this study are expected to be able to provide communication, information and education that is protective of employees so that motivation to work becomes even better.